Mixed bacterial culture mediated direct conversion of bio-glycerol to diols - Parate, Roopa; Mane, Rasika; Dharne, Mahesh; Rode, Chandrashekhar (Bioresource Technology, 2018)
Direct and economic transformation of biodiesel derived crude glycerol is gaining more significance. During screening of bacterial cultures Klebsiella pneumoniae and Enterobacter aerogenes were able to convert crude bio-glycerol to 2,3-butanediol (2,3-BDO) and 1,3-propanediol (1,3-PDO), as major compounds, ethanol and acetoin as minor compounds, with a conversion of 69% and 79% respectively. Process optimization could achieve maximum conversion at pH 7.0, 37 degrees C, 30-40 g/L glycerol and 1.5 g of inoculum until 120 h. Mixed cultures led to complete glycerol conversion with optimal yield and productivity. An innovative approach of using crude glycerol for sustained growth and tolerance of bacteria as source of carbon and energy makes this study more significant. In addition to this, a mixed culture concept introduced here is expected to make impact in process economics for industrial scale synthesis for direct transformation of glycerol into C3 and specifically, C4 diols.
Keywords: 1; 2; 3-Butanediol; 3-Propanediol; Bioconversion; Bioglycerol; Mixed culture

Bioglycerol (C3) upgrading to 2,3-butanediol (C4) by cell-free extracts of Enterobacter aerogenes NCIM 2695 - Parate, Roopa; Borgave, Mrunal; Dharne, Mahesh; Rode, Chandrashekhar (Journal of Chemical Technology and Biotechnology, 2021)
BACKGROUND Production of biobased chemicals from renewable resources is a green starring approach that serves as a substitute to petroleum derivatives. Bioglycerol, with its growing production as a co-product of biodiesel, is an attractive low-cost feedstock for the synthesis of platform chemicals by microbial fermentation. 2,3-butanediol (2,3-BDO) is amongst the top biorefinery platform chemicals that can be produced by glycerol fermentation. RESULTS The `Circular Economy' concept is demonstrated by converting the by-product bioglycerol using a cell-free extract of Enterobacter aerogenes NCIM 2695 (National Collection of Industrial Microorganisms, NCIM), yielding 22 g L-1 2,3-BDO, in 96 h, 98% atom economy and 0.4 g/g E factor. The cell-free bioglycerol conversion to 2,3-BDO was proved using a modified procedure for determining glycerol dehydrogenase enzyme assay by protein analysis and it was also shown to be cell-bounded. CONCLUSION Our study offers an effective utilization of the leftover material (i.e. cell-free extract) that biocatalysed C3 to C4 diol, which adds value to the overall economics of the process using only crude glycerol (C3) itself as a fermentative medium.
Keywords: 2; 3-Butanediol; atom economy; circular economy; E factor; Glycerol; glycerol dehydrogenase

Sustainable UV absorbing bio-plastic films by valorisation of humins and chitosan - Lucas, Nishita; Tambe, Snehal S.; Parate, Roopa; Hengne, Amol; Rode, C. V.; Athawale, Anjali A. (International Journal of Biological Macromolecules, 2025)
Humins, an inevitable bio-refinery waste by-product of sugar dehydration have been efficiently utilized for the first time for developing biodegradable thin films for UV shielding. The films were prepared from chitosan, and humins, a novel combination, aiming towards simultaneous utilization of marine and bio-refinery waste, rendering simple, effective, robust UV absorbing films. The structure-activity relationship of these films were elucidated with the help of different analytical techniques like X-ray diffraction, Fourier transform infrared spectroscopy, Thermogravimetric analysis, UV-vis spectroscopy, Atomic force microscopy, Scanning electron microscopy, Tensile testing, Contact angle measurements and water absorption studies. Intrinsic biodegradability was studied using fungi i.e. Aspergillus niger. Different feedstocks (corncob, rice husk, glucose and xylose) were explored for generating humins. Amongst them, humins derived from xylose were utilized for the preparation of the bio-plastic films of chitosan. The results revealed that, addition of 5.0 % humins was observed to be an optimum concentration yielding films with excellent UV absorption, mechanical properties, and biodegradability. The current work is in perfect alignment with sustainability and green chemistry as it ameliorates waste valorization (lignocellulosic and marine altogether). Further, its innovation stems from the first-hand use of humins for UV absorption, novel combination of biopolymers, use of green raw materials.
Keywords: biodegradable; Chitosan; Humins; Thin films; UV absorption; Waste valorization